The Influence of Leadership Style on the Performance of Educators and Educational Staff at the Faculty of FTIK, IAIN Bukittinggi - Sulaiman Sulaiman; Aniswita Aniswita; Nurhizrah Gistituati; Rusdinal Rusdinal (International Journal of Educational Management and Innovation, 2022)
The purpose of this study was to examine the effect of leadership style on the performance of educators and education staff at the Faculty of Tarbiyah and Teacher Training (FTIK) IAIN Bukittinggi. The population in this study were all educators and education staff at the FTIK IAIN Bukittinggi, totaling 75 people and 37 people randomly selected. Data were collected using questionnaires, leadership style questionnaires, and performance points. The data collected was processed using regression analysis. Researchers use the help of SPSS software. The results showed that the regression model formed was Y = 180,638+0.398 X with a 23.3% influence contribution. Based on the results of hypothesis testing, a significance value of 0.003 < 0.05 was obtained. Based on the teaching and academic staff of FTIK IAIN Bukittinggi in the excellent category. The ability of educators and education staff of FTIK IAIN Bukittinggi in achieving work results at the stipulated time is one indicator of the success of the FTIK IAIN Bukittinggi leadership in leading. A leader is also essential to provide encouragement or work motivation to employees or their subordinates to perform as proactive and successful employees.